2005
DOI: 10.1089/thy.2005.15.152
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Thyroid Microcarcinoma Found in Autopsy Series Conducted in Areas of Different Iodine Intake

Abstract: The prevalence of thyroid microcarcinomas found at autopsies is 100-1000 times higher than in clinical cancer. The epidemiological and histological characteristics of thyroid microcarcinomas in consecutive series of autopsies performed in two areas of different iodine intake were investigated. Iodine deficient (ID) area: n = 222 (M = 109, F = 113), median age: 74-76 years, median iodine excretion (MIE) of nursing home residents from this area: 70 microg/g creatinine. Iodine sufficient (IS) area: n = 221 (M = 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
1
6

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(51 citation statements)
references
References 16 publications
2
42
1
6
Order By: Relevance
“…In a single ethnic group, it has been observed that the autopsy prevalence of PTMC was not affected by iodine intake (80).…”
Section: Autopsy Prevalencementioning
confidence: 99%
See 1 more Smart Citation
“…In a single ethnic group, it has been observed that the autopsy prevalence of PTMC was not affected by iodine intake (80).…”
Section: Autopsy Prevalencementioning
confidence: 99%
“…This may be related to radiation exposure during the bombing of Hiroshima and Nagasaki, but is probably due to ethnicity since Japanese residing in Hawaii, not exposed to bomb radiation, have a similar prevalence of thyroid microcarcinoma, 24% (37,79). In 4620 autopsy cases, PTMC was observed in 9.9% when only a suspected lesion was examined and in 15.5% of 1262 autopsy cases when the entire gland was examined (13,29,37,59,75,76,(80)(81)(82)(83)(84)(85). Therefore, the prevalence of occult thyroid microcarcinoma increases with the extent of the examination of the thyroid, in particular with the thinness of the anatomical slices of the thyroid specimens (29).…”
Section: Autopsy Prevalencementioning
confidence: 99%
“…The improvement in diagnostic tools (image procedures and fineneedle aspiration biopsy) (Colonna et al, 2007;Scheiden et al, 2006) and greater extensiveness and number of thyroidectomies performed, which makes it easier to detect MPTCs (Leenhardt et al, 2004a), has been suspected to be of etiological importance in the observed increase of papillary thyroid cancer. One study (Kovacs et al, 2005) estimated the prevalence of thyroid microcarcinomas found at autopsies is 100-1000 times higher than in clinical cancer; they were not related to iodine intake and were exclusively of the papillary type (MPTC). It suggests that a large proportion of the population probably lives with undetected thyroid cancer and fits with the hypothesis of an apparent increase in thyroid cancer incidence.…”
Section: Discussionmentioning
confidence: 99%
“…The second form is a "silent PTMC," a tumor incidentally discovered that will never be apparent and that may be in concordance with the occult carcinoma detected in thyroid glands from autopsies. In this regard, it is interesting to note that gender distribution of PTMC found in autopsies shows differences as compared to clinical papillary tumors [Kovács et al, 2005]. It is well established that the incidence of PTC in women is significantly higher than that in men (with a female to male ratio greater than 2 to 1) [Yao et al, 2011].…”
Section: Age In Ptmcmentioning
confidence: 96%
“…It is well established that the incidence of PTC in women is significantly higher than that in men (with a female to male ratio greater than 2 to 1) [Yao et al, 2011]. However, several authors have not found any significant gender-related differences in PTMC found at autopsies [Lang et al, 1988;Neuhold et al, 2001;Kovács et al, 2005].…”
Section: Age In Ptmcmentioning
confidence: 99%